Topics at the left edge of infinitive clauses in Spanish and Catalan - Fernández-Sánchez, Javier (Borealis – An International Journal of Hispanic Linguistics, 2016)
This paper deals with clitic left dislocation (CLLD) in infinitive clauses (IC) in Spanish and Catalan. The goal of this paper is twofold. First, I provide evidence that CLLDed constituents can target the left edge of ICs, contrary to previous claims in the literature (e.g. Ojea 2013). The results should not be surprising, considering that Romance CLLD is not a Main Clause Phenomena (Jiménez-Fernández & Miyagawa 2013, Authier & Haegeman 2015). Second, this sets aside CLLD from other left peripheral fronting operations in these languages, which are systematically unavailable at the left edge of IC. I argue that the data presented here does not obviously follow from any current approach about the deficiency of non-finite domains. I defend, instead, that the data can be accounted for under Ott (2015)'s proposal about CLLD, where the dislocated constituent is the remnant of a clause ellipsis operation and it is paratactically integrated in the host clause. Further, I will speculate about how this approach can account for the linear positions where CLLDed phrases can occur.